Design and Development of the Restaurant X Reservation Application on the iOS Platform using App Clip - Rochella, Megan; Tileng, Kartika Gianina (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2026)
The food and beverage industry in Indonesia has shown significant growth, with 4.85 million business units in 2023. However, many restaurants still rely on manual reservation systems, which hinder operational efficiency. Despite internet penetration reaching 79.5%, with smartphones as the primary access device (83.39%), mobile application adoption faces barriers due to friction in the installation process. This study aims to design and implement an iOS-based restaurant reservation application using App Clips technology, integrated with a real-time admin dashboard. The system was developed using the MVVM architecture, with Swift and SwiftUI for the user interface, Golang for the backend, and PostgreSQL for the database. The system includes a customer-facing reservation app, a restaurant-side reservation management app, advance payment via QRIS displayed through the app, table selection based on customer ambience preferences, an automatic overbooking prevention mechanism, and finalization of reservations once the allotted time is complete. Development evaluation was conducted using task-based usability testing with seven respondents (four admins and three customers). The results showed a 100% task completion rate on both interfaces, exceeding the benchmark average of 78%, while App Clip access successfully demonstrated its effectiveness as a quick-access method without installation. This study contributes to the documentation of App Clip implementation in mobile reservation systems and presents an integrated reservation management solution that can be adapted to other sectors within the hospitality industry.